Assessment of Pesticide Residues in Flesh of Catla catla from Ravi River, Pakistan - Mobeen Akhtar; Shahid Mahboob; Salma Sultana; Tayyaba Sultana; Khalid Abdullah Alghanim; Zubair Ahmed (The Scientific World Journal)
The levels of dichlorodiphenyltrichloroethane (DDT), dichlorodiphenyldichloroethylene (DDE), endosulfan, endosulfan sulfate, carbofuran, and cartap which were estimated in the flesh of Catla catla sampled from ten sites of Ravi River between its stretches from Shahdara to Head Balloki were studied to know the level of contamination of the selected pesticides by GC-ECD method. All fish samples were found contaminated with different concentrations of DDT, DDE, endosulfan, and carbofuran; however, DDT and DDE concentrations were more than the maximum residue limits (MRLs) about food standards, while endosulfan sulfate and cartap were not detected. Pesticide concentrations in the fish flesh were ranged from 3.240 to 3.389 for DDT, 2.290 to 2.460 for DDE, 0.112 to 0.136 for endosulfan, and 0.260 to 0.370 μg g−1 for carbofuran. The findings revealed that the pesticide concentrations in the fish flesh decreased in the order: DDT > DDE > carbofuran > endosulfan. After Degh fall and After Hudiara nulla fall river sampling sites were found severely contaminated. It is proposed that a constant monitoring programs are needed to be initiated to overcome the present alarming situation.